The Effectiveness of Emergency Handling Protocol Education on Family Compliance in Initial Emergency Handling in Buni Bakti Village Rt 10/Rw 18, Babelan District, Bekasi Regency in 2025 - Cusmarih Cusmarih; Yusuf Saifull Amar (Jurnal Ners, 2026)
Emergency situations frequently occur in household settings and require prompt and appropriate responses to prevent serious health consequences. At the community level, families play a vital role as the first responders in emergency situations before professional medical assistance is available. The ability of families to handle emergencies appropriately is closely related to their level of knowledge, understanding, and preparedness regarding emergency handling protocols. However, in many communities, limited access to health education and insufficient exposure to emergency preparedness training may lead to low family compliance in implementing emergency handling protocols. This condition highlights the importance of providing structured emergency handling protocol education to improve family compliance and readiness in managing emergency situations at the household level. This study aimed to determine the effectiveness of emergency handling protocol education on family compliance in emergency situations in Buni Bakti Village, Bekasi Regency. This study employed a quantitative approach using a quasi-experimental design with a one-group pretest–posttest method. The research was conducted in Buni Bakti Village, RT 10/RW 18, Babelan District, Bekasi Regency, from October to December 2025. A total of 47 family respondents were selected using purposive sampling. The educational intervention consisted of counseling, demonstrations, and distribution of educational leaflets regarding emergency handling protocols based on the Indonesian Ministry of Health guidelines. Data were collected using a validated family compliance questionnaire and analyzed using the Wilcoxon Signed Rank Test. The results showed that family compliance before the educational intervention varied, with several respondents categorized as moderately compliant or non-compliant. After the intervention, all respondents demonstrated a high level of compliance. Statistical analysis indicated a significant difference in family compliance before and after the educational intervention (p < 0.05). Emergency handling protocol education was proven to be effective in improving family compliance in managing emergency situations at the household level. The educational intervention enhanced families’ understanding, readiness, and adherence to standardized emergency handling procedures, enabling them to respond more appropriately before professional medical assistance is available. These findings indicate that emergency education plays an important role in strengthening family preparedness and supporting effective emergency management within the community. Based on the findings of this study, it is recommended that emergency handling protocol education be implemented continuously and in a structured manner at the community level. Health workers and local health institutions are encouraged to integrate emergency education programs into routine community health activities to improve family preparedness and compliance. In addition, future studies are suggested to explore the effectiveness of different educational methods, involve larger samples, and include additional variables that may influence family compliance in emergency situations.